AN IN VITRO COMPARISION OF BOND STRENGTH OF PRECOATED AND UNCOATED BRACKETS USING SELF ETCHING PRIMER (Journal of Pharmaceutical Negative Results, 2022)
Aim: To test the hypothesis that there is no significant difference in the shear bond strength and the adhesive remnant on the tooth after debonding between precoated and uncoated brackets using a self etching primer.Materials and Methods: Adhesive Pre Coated Plus brackets, Uncoated brackets, Transbond XT adhesive and Transbond Plus self etching primer (TPSEP) were used in this study. The brackets were bonded to intact human premolar teeth. All the samples were divided into two groups --Group 1 (Uncoated brackets + Transbond Self Etching Primer + Transbond XT) & Group 2 (Adhesive Precoated Brackets + Transbond Self Etching Primer). Universal Testing Machine was used for calculating the shear bond strength of all samples. Image analysis equipment was used to measure the adhesive remnant on each tooth after debonding. Scanning Electron Microscope was used for this purpose.Results: Group 1 (Uncoated brackets + Transbond Self Etching Primer + Transbond XT) & Group 2 (Adhesive Precoated Brackets + Transbond Self Etching Primer) had nearly equal mean shear bond strength which is 8.86 +2.14 Mpa for precoated while 9.08 + 2.76 Mpa for the uncoated group. Statistically both the groups have almost same shear bond strength and significant difference was absent. In percentage of adhesive remnant also statistical difference between group 1 & group 2 was absent.Conclusion: There was no significant difference in the shear bond strength and the adhesive remnant on the tooth after debonding between precoated and uncoated brackets using a self etching primer.